Matirāma-makaranda, arthāt, Mahākavi Matirāma ke jīvana-carita, kāvyālocana evaṃ Rasarāja, Lalita-lalāma aura Matirāma-Satasaī kā saṅkshipta sarasa saṅgraha - Siṃha, Haradayālu, 1893-1951 (SAMP early 20th-century Indian books project ;, 1939)
On the life and works of Matirāma, 17th cent., Awadhi author.